Darwin's Doubt Defended: Why Evolution Supports Skepticism. - Littmann, Greg (Philosophical Papers, 2011)
Since the time of Charles Darwin, there has been concern that the theory of evolution provides fuel for skepticism. This paper presents new arguments that humanity's evolutionary origins are grounds for accepting that the universe is not as it appears to be to us. Firstly, it is argued that we should expect to have an incomplete capacity to comprehend the universe: both the mental limitations of all non-human life and the narrow interests of most humans provide evidence for this. Secondly, it is argued that we should expect the universe as it appears to us to have nothing more than a relationship of correlation to the universe as it actually is: both simplicity and the huge number of ways in which the universe may be represented provide reason for evolution to produce such a correlative system.